PENGARUH NILAI PELANGGAN DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN JASA EKSPEDISI POS INDONESIA - Iswatun Chasanah (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to analyze the effect of customer value and brand image on customer satisfaction of Pos Indonesia expedition services for students of the Faculty of Economics, University of Sarjanawiyata Tamansiswa Yogyakarta. This research is a field research which aims to see the relationship between variables. The sampling method is nonprobability, and the sampling technique uses accidental sampling and the sample used is 336 respondents. Data were analyzed using multiple linear regression. The results showed that customer value had a positive and significant effect on customer satisfaction. Brand image has a positive and significant effect on customer satisfaction. Customer value and brand image simultaneously have a positive and significant effect on customer satisfaction.